The Impact of Carbon Emission Disclosure on Firm Value - Aulia, Arti Mirza; Safitri, Uhti Noer Choliza; Hwihanus, Hwihanus (Indonesian Journal Publisher, 2024)
This study illustrates the importance of corporate disclosure of carbon emissions as a strategy to increase firm value in a global context that is increasingly concerned with sustainability. Through a meta-analysis of five international journals, findings show that carbon emissions disclosure is positively correlated with increased firm value in several Asian countries such as Korea and Taiwan, where this transparency is supported by strict government oversight and media attention to environmental policies. However, challenges arise in China, where a lack of responsiveness to economic transformation and inadequate disclosure practices can negatively impact firm value by hindering access to funding and firms' risk management capabilities. The implementation of international standards such as ISO 14064 in carbon emissions management was also emphasized as key to improving transparency, corporate reputation in terms of sustainability, and attractiveness to investors who are increasingly prioritizing sustainable business practices.